Persistent Developmental Limits to Devising Policy Innovation for Innovation Policies in Emerging Economies - Defny Holidin (Policy & Governance Review, 2022)
Promising industrial profiles of Southeast Asian emerging economies have met their developmental limits in the face of the Asian Financial Crisis in the late 1990s. However, following the crisis, they have not been successful in upscaling the technological competitiveness of their industries. By applying the national innovation system approach originally developed in advanced western economies as an institutional mechanism of policy innovation in light of developmentalism, I seek to explain these persistent developmental limits in Malaysia and Indonesia. My qualitative research examines literature discussing policy coordination mechanisms in innovation policies and policy documents containing coordination mechanisms involving firms, universities, and government agencies; then, how these issues implicate innovation policies in the two countries. I employ a comparative institutional analysis between them focusing on institutional characteristics of the national innovation systems, specifically their institutional obstacles occurring within development paths amidst prevailing political environments. I suggest that persistent developmental limits in Malaysia and Indonesia result from systemic failures of achieving developmental aims regardless of their politico-administrative regimes. Existing institutional frameworks of the national innovation systems, entrenched in the socio-economic prevalence of the two countries, have not fit the nations’ developmental aims pursued upon innovation upgrading.